Multicilia dynamically transduce Sonic Hedgehog signaling to regulate choroid plexus functions - Suifang Mao; Rui Song; Shibo Jin; Song Pang; Aleksandra Jovanovic; Adam Zimmerman; Peng Li; Xinying Wu; Michael F. Wendland; Kerry Lin; Wei-Chi Chen; Semil P. Choksi; et al. (Cell Reports)
Summary: The choroid plexus is a major site for cerebrospinal fluid (CSF) production, characterized by a multiciliated epithelial monolayer that regulates CSF production. We demonstrate that defective choroid plexus ciliogenesis or intraflagellar transport yields neonatal hydrocephalus, at least in part due to increased water channel Aqp1 and ion transporter Atp1a2 expression. We demonstrate choroid plexus multicilia as sensory cilia, transducing both canonical and non-canonical Sonic Hedgehog (Shh) signaling. Interestingly, it is the non-canonical Shh signaling that represses Aqp1 and Atp1a2 expression by the Smoothened (Smo)/Gαi/cyclic AMP (cAMP) pathway. Choroid plexus multicilia exhibit unique ciliary ultrastructure, carrying features of both primary and motile cilia. Unlike most cilia that elongate during maturation, choroid plexus ciliary length decreases during development, causing a decline of Shh signaling intensity in the developing choroid plexus, a derepression of Aqp1 and Atp1a2, and, ultimately, increased CSF production. Hence, the developmental dynamics of choroid plexus multicilia dampens the Shh signaling intensity to promote CSF production.